City-regional cooperation in smaller metropolitan areas. Transdisciplinary research on strategy development in the city region of Kiel (Germany) - Priebs, Axel; Wehrhahn, Rainer (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
This paper presents the results of a transdisciplinary study on the further development of city-regional cooperation in a smaller metropolitan region. The case study covers the city region of Kiel in the state of Schleswig-Holstein, Germany. Against the backdrop of scientific concepts on city-regional cooperation and based on the own empirical research, central future topics of regional cooperation and possible forms of institutional development were identified in the study. It was recommended to begin via a regional special purpose association (“Zweckverband”), allowing for later refinement options, which were introduced in the form of scenarios. This approach was supported by key decision-makers, but also encountered resistance from stakeholders who were reluctant to give up familiar structures. Beyond the case study, general challenges for approaches to more intensive cooperation in city-regions are identified. Therewith, the study can contribute to current governance research in urban-rural processes.